Deploying an Inter‐European Quantum Network. Issue 2 (14th December 2022) - Ribezzo, Domenico; Zahidy, Mujtaba; Vagniluca, Ilaria; Biagi, Nicola; Francesconi, Saverio; Occhipinti, Tommaso; Oxenløwe, Leif K.; Lončarić, Martin; Cvitić, Ivan; Stipčević, Mario; Pušavec, Žiga; Kaltenbaek, Rainer; et al.
Abstract: Around 40 years have passed since the first pioneering works introduced the possibility of using quantum physics to enhance communications safety. Nowadays, quantum key distribution (QKD) exited the physics laboratories to become a mature technology, triggering the attention of States, military forces, banks, and private corporations. This work takes on the challenge of bringing QKD closer to a consumer technology: deployed optical fibers by telecommunication companies of different States have been used to realize a quantum network, the first‐ever connecting three different countries. This work also emphasizes the necessity of networks where QKD can come up besides classical communications, whose coexistence currently represents the main limitation of this technology. This network connects Trieste to Rijeka and Ljubljana via a trusted node in Postojna. A key rate of over 3 kbps in the shortest link and a 7‐hour‐long measurement demonstrate the system's stability and reliability. The network has been used to present the QKD at the G20 Digital Ministers' Meeting in Trieste. The experimental results, together with the interest that one of the most important events of international politics has attracted, showcase the maturity of the QKD technology bundle, placing it in the spotlight for consumer applications in the near term. Abstract : Quantum key distribution (QKD) is today a mature consumer technology, but, even if many quantum networks have been already established in the world, Europe still has none. In this work a quantum network connecting Italy, Slovenia, and Croatia has been realized, the first‐ever among three countries, and representing the first step toward a European quantum infrastructure (EuroQCI).